POLITINĖS FILOSOFIJOS IR POLITIKOS MOKSLO SANTYKIS: LEO STRAUSSO POZICIJA. - Stoškus, Mindaugas (Problems / Problemos, 2011)
The aim of this article is to discuss the relation between political philosophy and political science. The development of political science highlighted two main approaches toward this relation. One group of political scientists says that political science must stay close to political philosophy while another group demands strict dissociation. Behaviorism in political science marked the enormous growth of influence of the later group. Leo Straus appeared as a rigid critic of behavioral political science and an influential defender of political philosophy. This paper deals with his criticism of basic premises of political science and his attitude to the significance of political philosophy.